2000
DOI: 10.1021/bi9917885
|View full text |Cite
|
Sign up to set email alerts
|

Aminoglycoside−Arginine Conjugates That Bind TAR RNA:  Synthesis, Characterization, and Antiviral Activity

Abstract: Regulation of HIV gene expression is crucially dependent on binding of the trans-activator protein, Tat, to the trans-activation response RNA element, TAR, found at the 5′ end of all HIV-1 transcripts. Tat-TAR interaction is mediated by a short arginine-rich domain of the protein. Disruption of this interaction could, in theory, create a state of complete viral latency. A new class of small-molecule peptidomimetic TAR RNA binders, conjugates of aminoglycosides and arginine, was recently designed [Litovchick, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
84
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 62 publications
(130 reference statements)
5
84
0
Order By: Relevance
“…EMSA demonstrating the ability of NeoR to trap 80S complexes on an mRNA template+ Ribosome binding assays were performed in wheat germ extracts with 32 P-labeled mRNA (50,000 cpm/reaction) in the presence of GMP-PNP (lane 1), cycloheximide (Chx; lane 2), cycloheximide and NeoR (lane 3), and 10 mM NeoR (lane 4)+ Complexes were resolved by polyacrylamide gel electrophoresis on native gels using conditions previously described (Lorsch & Herschlag, 1999)+ Following electrophoresis, the gel was dried and exposed to X-OMAT X-ray film (Kodak) at Ϫ70 8C with an intensifying screen+ The positions of migration of the 48S and 80S complexes are indicated by arrows, as is the position of the wells of the gel+ The asterisk indicates a complex whose identity is not known (possibly a 40S ϩ 80S complex) and that may correspond to the complexes present in the shoulder observed at fraction #15 of Figure 6A+ 1276 M. Carriere et al Aminoglycosides interact in complex ways with the prokaryotic ribosome+ They interfere with A-site function and some stimulate misreading of the mRNA template, resulting in the incorporation of the wrong amino acid + Neomycin and hygromycin have also been reported to block translocation (Hausner et al+, 1988) and more recently, neomycin and paromomycin have been shown to inhibit 30S ribosomal subunit assembly (Mehta & Champney, 2002)+ Given the steric bulk of AACs, as well as the presence of multiple arginine functional groups (compared to aminoglycosides), we suspect that AACs interact with a different site on the ribosome+ Our studies have not addressed the nature or location of the AAC binding site, but they could bind to either or both ribosomal subunits+ Binding to the 40S subunit could be feasible if induced structural changes altered activity of the peptidyl transferase site of the 60S subunit+ It will be interesting to test these possibilities in future experiments+ Additional properties of AACs include inhibition of Tat/ Tar interaction (Litovchick et al+, 2000), downregulation of the chemokine CXC receptor type 4 (Litovchick et al+, 2001), and inhibition of bacterial RNase P (Eubank et al+, 2002), suggesting that AACs (especially NeoR) could be considered for both HIV and bacterial chemotherapy+ In this report, we now demonstrate that AACs can inhibit eukaryotic translation+ We do not know if these activities of AACs are intimately linked or can be separated into different activities of the AACs+ Clearly, in-depth structure-activity relationship studies could help assign the different properties to functional groups+…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMSA demonstrating the ability of NeoR to trap 80S complexes on an mRNA template+ Ribosome binding assays were performed in wheat germ extracts with 32 P-labeled mRNA (50,000 cpm/reaction) in the presence of GMP-PNP (lane 1), cycloheximide (Chx; lane 2), cycloheximide and NeoR (lane 3), and 10 mM NeoR (lane 4)+ Complexes were resolved by polyacrylamide gel electrophoresis on native gels using conditions previously described (Lorsch & Herschlag, 1999)+ Following electrophoresis, the gel was dried and exposed to X-OMAT X-ray film (Kodak) at Ϫ70 8C with an intensifying screen+ The positions of migration of the 48S and 80S complexes are indicated by arrows, as is the position of the wells of the gel+ The asterisk indicates a complex whose identity is not known (possibly a 40S ϩ 80S complex) and that may correspond to the complexes present in the shoulder observed at fraction #15 of Figure 6A+ 1276 M. Carriere et al Aminoglycosides interact in complex ways with the prokaryotic ribosome+ They interfere with A-site function and some stimulate misreading of the mRNA template, resulting in the incorporation of the wrong amino acid + Neomycin and hygromycin have also been reported to block translocation (Hausner et al+, 1988) and more recently, neomycin and paromomycin have been shown to inhibit 30S ribosomal subunit assembly (Mehta & Champney, 2002)+ Given the steric bulk of AACs, as well as the presence of multiple arginine functional groups (compared to aminoglycosides), we suspect that AACs interact with a different site on the ribosome+ Our studies have not addressed the nature or location of the AAC binding site, but they could bind to either or both ribosomal subunits+ Binding to the 40S subunit could be feasible if induced structural changes altered activity of the peptidyl transferase site of the 60S subunit+ It will be interesting to test these possibilities in future experiments+ Additional properties of AACs include inhibition of Tat/ Tar interaction (Litovchick et al+, 2000), downregulation of the chemokine CXC receptor type 4 (Litovchick et al+, 2001), and inhibition of bacterial RNase P (Eubank et al+, 2002), suggesting that AACs (especially NeoR) could be considered for both HIV and bacterial chemotherapy+ In this report, we now demonstrate that AACs can inhibit eukaryotic translation+ We do not know if these activities of AACs are intimately linked or can be separated into different activities of the AACs+ Clearly, in-depth structure-activity relationship studies could help assign the different properties to functional groups+…”
Section: Discussionmentioning
confidence: 99%
“…The procedures for the synthesis and purification of NeoR and R3G have been detailed (Litovchick et al+, 2000(Litovchick et al+, , 2001)+ Synthesis and chemical characterization of NeoR1, NeoR2, NeaMR1, NeaMR4, ParomoR1, and ParomoR4 will be published elsewhere+ Neomycin B was purchased from Fluka+ Gentamicin and L-arginine were obtained from Sigma+ The peptides RRGGRRGGRR and RRGRRGRR were purchased from American Peptide Company, Inc+ (Sunnyvale, California) and characterized by RP-HPLC and mass spectral analysis+ Peptides were .97% pure+…”
Section: Synthesis Of Aminoglycoside-arginine Conjugatesmentioning
confidence: 99%
“…One such target is the human immunodeficiency virus (HIV) 1 trans activation responsive (TAR) RNA ( Figure 1A) whose binding to the Tat protein is essential for production of fulllength RNA transcripts during viral replication (3,4). Small molecules that disrupt this interaction have been shown to display antiviral activity in vitro (5).…”
mentioning
confidence: 99%
“…Even today, the importance of aminoglycosides is not diminished, e.g., in the treatment of infections associated with HIV. 6) Relative to their chemical structure, aminoglycosides can be classified into two major groups. The first is composed of those having an aglycone of fully-substituted aminocyclitol synthesized from myo-inositol.…”
mentioning
confidence: 99%